Mobilização política urbana e o uso das Tics: um estudo exploratório em Jundiaí-sp - Aquino, Pedro Miranda de (2011)
The research aimed to understand the processes involved in articulating the Comitê Cidade Democrática de Jundiaí. This group has began its activities in August 2009 and was inittialy intended to disclose the Cidade Democrática website, so that the increased citizen participation could promote the changes they expected in the city of Jundiaí. The fact that the group has made extensive use of digital resources is sufficient to note the extraordinary nature of the case and let us decide on an exploratory series of the political phenoma occurring in Jundiaí. Thus, it was expected to contribute to the discipline of social psychology, especially in the research area of Political Psychology and Social Movements. The analysis of the data collected verified the functionality of the website for the citizen collaboration, also, the limits and possibilities of the Comittee to mobilize citizens are demonstrated, and the lack of responsiveness of local goverment was pointed